2018
DOI: 10.1111/bjh.15565
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand factor clearance – biological mechanisms and clinical significance

Abstract: The mechanisms involved in regulating von Willebrand factor (VWF) clearance remain poorly understood. However recent studies have shown that macrophages play a critical role in regulating the half-life of VWF, and have identified specific lectin (including asialoglycoprotein, macrophage galactose-type lectin, Sigec-5 and C-type lectin domain family 4 member M) and scavenger receptors (including low-density lipoprotein receptor-related protein-1, scavenger receptor A1 and stabilin-2) that are involved in VWF cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 83 publications
(145 reference statements)
5
69
0
1
Order By: Relevance
“…A recent meta-analysis of 11 independent genome-wide association studies (GWASs) [56] revealed that blood group O determines low VWF independently of A and B antigens; moreover, A and B antigens may also determine higher plasma VWF. Moreover, individuals with blood group O have slightly increased VWF clearance [57], which is probably another determinant of lower VWF in subjects with this blood type and, consistently, the largest collaborative studies on VWD have found slightly increased VWF clearance in a significant proportion of type 1 VWD patients [58]. This would be an additional mechanism in the pathogenesis of this disorder.…”
Section: Difficulties With Diagnosis Of Type 1vwdmentioning
confidence: 91%
See 3 more Smart Citations
“…A recent meta-analysis of 11 independent genome-wide association studies (GWASs) [56] revealed that blood group O determines low VWF independently of A and B antigens; moreover, A and B antigens may also determine higher plasma VWF. Moreover, individuals with blood group O have slightly increased VWF clearance [57], which is probably another determinant of lower VWF in subjects with this blood type and, consistently, the largest collaborative studies on VWD have found slightly increased VWF clearance in a significant proportion of type 1 VWD patients [58]. This would be an additional mechanism in the pathogenesis of this disorder.…”
Section: Difficulties With Diagnosis Of Type 1vwdmentioning
confidence: 91%
“…In this regard, VWF mutations associated with decreased VWF sialylation [59] and increased binding of VWF to LRP1 and SR-AI [60,61] have been associated with low VWF resembling the type 1 VWD phenotype, but with normal platelet and endothelial VWF [58]. Supporting these observations, large cohort studies have found a significant proportion of type 1 VWD patients with enhanced VWF clearance [39,62,63], which would be an additional mechanism of the disease.…”
Section: Difficulties With Diagnosis Of Type 1vwdmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative abnormalities in plasma levels of coagulation factors, including the multimeric glycoprotein von Willebrand factor (VWF) can associate with either bleeding disorders (von Willebrand disease, VWD) or increase the risk for thrombosis . Plasma levels of VWF can be modified by pathways that regulate its synthesis or secretion from endothelial cells or megakaryocytes, or clearance, which involves a series of semiselective ligand‐receptor mediated interactions involving hepatocytes, macrophages, and endothelial cells in the liver and/or spleen …”
Section: Introductionmentioning
confidence: 99%